A transgenic platform for testing drugs intended for reversal of cardiac remodeling identifies a novel 11βHSD1 inhibitor rescuing hypertrophy independently of re-vascularization. - Oren Gordon (Public Library of Science (PLoS), 2014)
Rationale Rescuing adverse myocardial remodeling is an unmet clinical goal and, correspondingly, pharmacological means for its intended reversal are urgently needed. Objectives To harness a newly-developed experimental model recapitulating progressive heart failure development for the discovery of new drugs capable of reversing adverse remodeling. Methods and results A VEGF-based conditional transgenic system was employed in which an induced perfusion deficit and a resultant compromised cardiac function lead to progressive remodeling and eventually heart failure. Ability of candidate drugs administered at sequential remodeling stages to reverse hypertrophy, enlarged LV size and improve cardiac function was monitored. Arguing for clinical relevance of the experimental system, clinically-used drugs operating on the Renin-Angiotensin-Aldosterone-System (RAAS), namely, the ACE inhibitor Enalapril and the direct renin inhibitor Aliskerin fully reversed remodeling. Remodeling reversal by these drugs was not accompanied by neovascularization and reached a point-of-no-return. Similarly, the PPARγ agonist Pioglitazone was proven capable of reversing all aspects of cardiac remodeling without affecting the vasculature. Extending the arsenal of remodeling-reversing drugs to pathways other than RAAS, a specific inhibitor of 11β-hydroxy-steroid dehydrogenase type 1 (11β HSD1), a key enzyme required for generating active glucocorticoids, fully rescued myocardial hypertrophy. This was associated with mitigating the hypertrophy-associated gene signature, including reversing the myosin heavy chain isoform switch but in a pattern distinguishable from that associated with neovascularization-induced reversal. Conclusions A system was developed suitable for identifying novel remodeling-reversing drugs operating in different pathways and for gaining insights into their mechanisms of action, exemplified here by uncoupling their vascular affects.